Fertiliser use and soil carbon sequestration: Key messages for climate change mitigation strategies - Hijbeek, Renske; Loon, Marloes P. van; Wollenberg, Eva Karoline; White, Julianna M.; Ittersum, Martin K. van (2019)
Reducing greenhouse gas (GHG) emissions and increasing soil or biomass carbon stocks are the main agricultural pathways to mitigate climate change. Scientific and policy attention has recently turned to evaluating the potential of practices that can increase soil carbon sequestration. Forty percent of the world’s soils are used as cropland and grassland, therefore agricultural policies and practices are critical to maintaining or increasing the global soil carbon pool. This info note explains the current understanding of the impact of mineral fertiliser use on soil carbon sequestration as a mitigation strategy in agriculture. The science and understanding on soil carbon sequestration and mitigation is still emerging, especially in tropical regions. Taking this into consideration, this info note discusses related effects of fertiliser use on climate change mitigation, such as nitrous oxide (N2O) and carbon dioxide (CO2) emissions from nitrogen fertiliser use and production, and the potential effects of mineral fertiliser use on land use change.